Mayoral referendums and elections - Rallings, Colin; Cowling, David; Thrasher, Michael (2002)
The principle of directly elected mayors forms a key part of the Labour government's strategy to modernise local democracy and strengthen accountability. First applied to London, the government has sought to extend the institution, allowing local referendums to determine whether the public favours the principle or not. This article examines the state of public opinion regarding elected mayors before reporting on the outcome of referendums held since the 2001 general election. We then consider the results of mayoral elections, specifically addressing issues of electoral participation, legitimation and partisan support. In conclusion, we consider whether its experience with both referendums and mayoral elections may have affected the government's enthusiasm for further expansion of this institution across the local government system. - Reproduced.
Keywords: Referendum; Elections; Mayor; Local government